Purchasing Practices of Food, clothing and Consumer Durables among Farm Families of Gadag District - Sumangala, P. R.; Uppar, Yallawwa (Indian Journal of Marketing, 2009)
Everyone who spends money to buy goods and services from the market is a buyer, but a buyer who makes use of goods and services for his/her living to maintain a good physical and mental health is a consumer. A common man as a consumer has a wide range of expectations such as price, correct weight and measurement, purity or genuiness, packaging, service during and service after the sale.